Analisis Tingkat Kemiskinan Pada Rumah Tangga Miskin Kecamatan Cibal Kabupaten Manggarai - Bonefasius Berdi; Yosefa Maria Juita Hale; Donatus Magas (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the poverty rate in Cibal District, Manggarai Regency based on the characteristics of poor households. The data analysis techniques used are crosstabulation analysis and CHAID (Chi- Squared Automatic Interaction Detection /Detector) analysis. The results showed that, (1) based on 14 indicators of poor households from the Central Statistics Agency (BPS) the relationship between the status of poverty and the status of the head of the household in cibal sub-district is very weak (2) in general the dominant characteristics or indicators to distinguish poor households from non-poor households in cibal kecamtan are the types of building floors, the frequency of meals in a day, the source of drinking water, the floor area of the building is 8m2.